Science, Environmental, Technology, Society Approach (SETS) in Improving Science Literacy of Junior High School Students - Pramesti, Salsabila Aprillyanti; Rosdiana, Laily (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2024)
Science, Environmental, Technology, Society Approach (SETS) in Improving Science Literacy of Junior High School Students. This study aims to describe the implementation of science learning with the Science, Environmental, Technology, Society (SETS) approach, improving students' scientific literacy skills. This study uses a descriptive-quantitative research type with a group Pretest Posttest Design and involves 35 students of class VII-K SMP Negeri 1 Wonoayu as subjects. The research instrument is a science literacy test measured using the TOSLS Scientific Literacy indicators developed by Gormally from the Georgia Institute of Technology. The results showed a significant increase in students' scientific literacy with an N-Gain value of 0.74 which is included in the high category. In conclusion, the implementation of the SETS-Based Guided Inquiry Learning Model has proven effective in improving the scientific literacy of junior high school students.